The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12964-016-0152-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL-10 in Mycobacterium avium subsp. paratuberculosis infection

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) is an intracellular pathogen and is the causative agent of Johne’s disease of domestic and wild ruminants. Johne’s disease is characterized by chronic granulomatous enteritis leading to substantial economic losses to the livestock sector across the world. MAP persistently survives in phagocytic cells, most commonly in macrophages by disrupting its early antibacterial activity. MAP triggers several signaling pathways after attachment to pathogen recognition rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 166 publications
(197 reference statements)
0
44
0
Order By: Relevance
“…The TLR signaling pathways are one of the survival strategies that MAP uses to escape the host's defense mechanisms. For instance, following TLR2 recognition, MAP activates MAPK-p38, which results in an inhibition of phagosome maturation, independent to the upregulation of interleukin-10 (IL-10) (30,31). Other studies reported the role of metal transporters such as SLC11A1, which pumps out divalent cation from the phagosome as a host strategy to restrict pathogen growth by iron deprivation (32).…”
Section: Introductionmentioning
confidence: 99%
“…The TLR signaling pathways are one of the survival strategies that MAP uses to escape the host's defense mechanisms. For instance, following TLR2 recognition, MAP activates MAPK-p38, which results in an inhibition of phagosome maturation, independent to the upregulation of interleukin-10 (IL-10) (30,31). Other studies reported the role of metal transporters such as SLC11A1, which pumps out divalent cation from the phagosome as a host strategy to restrict pathogen growth by iron deprivation (32).…”
Section: Introductionmentioning
confidence: 99%
“…as measured by qRT-PCR (Abenda et al 2013). This counteracted initial IL-12 production (Abenda et al 2013) and high levels of IL-10 in paratuberculosis were shown promote the survival of MAP (Hussain et al 2016 Manuscript to be reviewed expression was downregulated immediately after in vitro infection with MAP (Motiwala et al 2006). To our knowledge, the role of IL-12 in MAP infections of cows has not been analysed so far on protein level (Abenda et al 2013), but the IL-12 associated immune response should also be protective.…”
Section: Discussionmentioning
confidence: 95%
“…et al, 2017), as well as IL-12p40 (Cooper and Khader, 2007) are essential for the host immune counter against mycobacteria (Hossain and Norazmi, 2013). The interplay between IL-10, IL-12p40, and IL-6 intense affected the outcomes of macrophage function and bacterial infection (Hussain et al, 2016). The neutralization of IL-6 boosted the M. tuberculosis survival in T2DM mice (Cheekatla et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The human with deficient IL-12p40 is more susceptible to mycobacterial infection (Cooper and Khader, 2008). IL-10 is not only crucial immune-regulatory molecule, but also able to inhibit the anti-mycobacterial activity of macrophages (Nagata et al, 2010) including, blocking phagosomal maturation and apoptosis, and decreasing the production of pro-inflammatory cytokines, accounts for the intracellular survival of mycobacteria (Hussain et al, 2016). Consistently, we found that Ms_PE31 infected macrophages increased the production of anti-inflammatory cytokine IL-10, while decreased the production of specific pro-inflammatory cytokines IL-6 and IL-12p40, might be promoted to the survival of Ms_PE31 in macrophages and induces the other immune responses.…”
Section: Discussionmentioning
confidence: 99%